Exploração da Complementariedade Solar, Eólica e de Maré no Uso Eficiente de Contratos de Acessibilidade da Rede por Usinas Híbridas. - VERAS, Rafael Brito de Sousa (2022)
The growing concern with climate change coupled with the depletion of non-renewable energy sources has led to increased penetration of power generation through renewable and non-dispatchable sources in the global electricity mix. As these sources have intermittent and stochastic behavior, they inject complexity into the utilization and contracting of access to the transmission systems. One way to mitigate these undesirable characteristics of renewable sources is the hybridization of power plants through the joint generation between energy resources with intermittent characteristics that complement each other in time. In this work is proposed a methodology to evaluate the benefits brought to the efficient use of the for teh access contracts to transmission systems in Brazil by hybrid plants with solar, wind and tidal current generation in the region of Alcântara and São Luís, Maranhão. For the modeling of the plants were used wind speed and solar irradiance measurement data, added to a hydrodynamic simulation of the Boqueirão channel for the acquisition of tidal current speed data. Through the methodology developed, the performance of the modeled plants was evaluated in several parameters, such as transmission contract efficiency, overrun portion, firm power and fluctuation ratio. The results obtained lead to conclusions that confirm the benefits of diversifying renewable sources in the same power plant.